Female students’ experience in preventing scabies - Fithri Iradaty; Edy Suyanto; Budi Aji; Abdal Chaqil Harimi (Intelektual Pustaka Media Utama, 2021)
The purpose of this study was to examine the students' perceptions on the environmental health conditions related to the contagious skin disease of scabies and examine the implementation of clean and healthy behavior of the students. This research was done by adopting qualitative approach with phenomenological method. The qualitative data obtained were analyzed using thematic analysis with the help of the Maxqda 10 Program. The data were collected through purposive and snowball sampling techniques. The findings showed that the environmental sanitation of the Pesantren (Islamic boarding school) in some bedrooms are still not sufficiently ventilated and they needed clean water. The characteristics of Pesantren teaching which teaches students to live modestly, patiently, and prihatin (simple). The perceptions of Pesantren students about scabies that scabies was a normal thing to be experienced by students and that as long as the itching did not produce pus or blood it was not scabies. The healthy behavior of the students in this study were related with taking a bath, maintaining clean clothes, washing hands before eating of the students were still lacking. The efforts in improving the healthy living of the students was seen through the establishment of a health center in the Pesantren called Poskestren (Pesantren Health Services) but there were still limited facilities and the implementation of the administrators’ programs to prevent scabies is also seen to be not optimal yet.